1943
DOI: 10.1001/jama.1943.02840030015004
|View full text |Cite
|
Sign up to set email alerts
|

Management of Male Pubescence

Abstract: The period of pubescence and adolescence in a boy is frequently associated with physical and psychologic problems. Their solution frequently determines the effectiveness and happiness of the adult. It is the obligation of the general practitioner and pediatrician in cooperation with the school authorities, training centers for boys and the family to help solve these problems.1 This requires an understanding of the mechanisms of pubescence and the ability to recognize and manage adequately their normal and abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1943
1943
1951
1951

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Curiously enough, there has been little attention to such metrical indices as more especially signalize sexual dimorphism, for example shoulder and pelvic width, neck girth, etc. Recent papers by Borruat (1941) and by Schonfeld (1943) on, pubescence sufficiently emphasize how defective is our knowledge concerning sequence and duration of the several manifestations accompanying maturation of the male gonads. Most of the literature dealing with the male at present available is indeed of very doubtful scientific value by the very nature of the methods on which it relies.…”
Section: Introductionmentioning
confidence: 99%
“…Curiously enough, there has been little attention to such metrical indices as more especially signalize sexual dimorphism, for example shoulder and pelvic width, neck girth, etc. Recent papers by Borruat (1941) and by Schonfeld (1943) on, pubescence sufficiently emphasize how defective is our knowledge concerning sequence and duration of the several manifestations accompanying maturation of the male gonads. Most of the literature dealing with the male at present available is indeed of very doubtful scientific value by the very nature of the methods on which it relies.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro antibacterial studies showed tha4 (2) to explore the upper limits of dosage at which the mixture could be safely administered. The fact that the incidence of renal complications in the patients receiving these higher doses of the sulfadiazine-sulfamerazine combination was no greater than that observed in patients receiving the conventional doses of either sulfadiazine or sulfamerazine alone is in all probability due to the improvement in solubility gained by using a mixture of sulfonamide compounds.…”
mentioning
confidence: 99%